Peter and the secret of Rundoon - Barry, Dave.; Pearson, Ridley; Call, Greg (New York : Disney Editions/Hyperion Books for Children, 2007)
Fearing that the sinister Lord Ombra was not destroyed, Peter and Molly travel to the land of Rundoon, which is ruled by the evil King Zarboff.
Keywords: Adventure stories; Characters in literature -- Fiction; Islands -- Fiction; Characters in literature -- Juvenile fiction; Islands -- Juvenile fiction; Humorous fiction; Fantasy fiction; Adventure fiction